Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1002/cbic.200700433
|View full text |Cite
|
Sign up to set email alerts
|

Pyrazolyl–Diamine Ligands That Bear Anthracenyl Moieties and Their Rhenium(I) Tricarbonyl Complexes: Synthesis, Characterisation and DNA‐Binding Properties

Abstract: Two novel families of pyrazolyl-diamine ligands that bear an anthracen-9-yl group as a DNA-binding fragment, pz*(CH2)2NH(CH2)2NHCH2-9-anthryl (pz*=pz (L(1)), 3,5-Me2pz (L2)) and pz*(CH2)2NH(CH2)2NH(2 (pz*=4-(9-anthrylmethyl)pz (L3), 3,5-Me2-4-(9-anthrylmethyl)pz (L4)), have been prepared and fully characterised. In the case of L2-L4, the evaluation of their coordination capability towards the fac-[Re(CO)3]+ core led to the synthesis of the organometallic complexes fac-[Re(CO)(3){3,5-Me(2)pz(CH2)2NH(CH2)2NHCH2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…However, for the acridine orange ligand L 3 there was a change in the mobility of the plasmid DNA; this indicated that L 3 has a better ability than L 2 to interact with DNA. These findings are consistent with the results for L 2 Pt and L 3 Pt presented above: that is, a more probable contribution of the intercalation binding mode in the case of L 3 Pt reflecting a higher DNA affinity for the AO chromophore than for anthracene 8. 10…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…However, for the acridine orange ligand L 3 there was a change in the mobility of the plasmid DNA; this indicated that L 3 has a better ability than L 2 to interact with DNA. These findings are consistent with the results for L 2 Pt and L 3 Pt presented above: that is, a more probable contribution of the intercalation binding mode in the case of L 3 Pt reflecting a higher DNA affinity for the AO chromophore than for anthracene 8. 10…”
Section: Resultssupporting
confidence: 92%
“…Moreover, we have also shown that 99m Tc I tricarbonyl complexes anchored by pyrazolyl‐diamine ligands functionalized with polyaromatic DNA intercalators have the ability to target the nuclei of tumor cells, with some complexes causing significant cell killing at low radioactivity levels, mainly through apoptotic pathways 810. These encouraging results prompted us to study Pt II complexes anchored by pyrazolyl‐diamine chelators bearing planar and aromatic DNA‐intercalating groups.…”
Section: Introductionmentioning
confidence: 96%
“…73 Changes in the CD bands in this spectral range are useful to detect DNA conformational changes, damage and/or cleavage. 71,74,75 In addition, even if the complexes are not chiral and thus present no CD signal, their association with DNA may give rise to an induced circular dichroism spectra (ICD) in the range of the complexes´ absorption bands.…”
Section: Fluorescence Experimentsmentioning
confidence: 99%
“…Thereby, the Auger electrons emitted from the isomeric transition may become opportune for therapeutical purposes besides classical imaging. [92][93][94][95] In the context of combined fluorescence-radioimaging the metaldependent luminescence of rhenium amino-heterocycle complexes has been used to detect the localization of peptides on a cellular level. So-called single amino acid chelates (SAAC) were incorporated in the targeting fMLF sequence and then used for in vitro screening.…”
Section: Basic Chemistry Of [M(oh 2 ) 3 (Co) 3 ] + In Watermentioning
confidence: 99%